2016
DOI: 10.2147/copd.s103758
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-16-producing NK cells and T-cells in the blood of tobacco smokers with and without COPD

Abstract: BackgroundLong-term exposure to tobacco smoke causes local inflammation in the airways that involves not only innate immune cells, including NK cells, but also adaptive immune cells such as cytotoxic (CD8+) and helper (CD4+) T-cells. We have previously demonstrated that long-term tobacco smoking increases extracellular concentration of the CD4+-recruiting cytokine interleukin (IL)-16 locally in the airways. Here, we hypothesized that tobacco smoking alters IL-16 biology at the systemic level and that this effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…In the present study we found that the positive association of higher MPV and DM incidence was more pronounced in non-current smokers. Smoking was positively associated with increased MPV levels [ 36 ], inflammation [ 37 ] and immune response [ 38 ]. High levels of inflammation in current smokers and relative higher ratio of females in the non-smokers compared to the current smokers (69.2% vs. 6.7%) might contribute to the smoking-MPV interaction on incident DM risk.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we found that the positive association of higher MPV and DM incidence was more pronounced in non-current smokers. Smoking was positively associated with increased MPV levels [ 36 ], inflammation [ 37 ] and immune response [ 38 ]. High levels of inflammation in current smokers and relative higher ratio of females in the non-smokers compared to the current smokers (69.2% vs. 6.7%) might contribute to the smoking-MPV interaction on incident DM risk.…”
Section: Discussionmentioning
confidence: 99%
“…NK cells from long-term smokers display a decreased intracellular IL-16 concentration. This depletion of the CD4+-recruiting cytokine strongly suggests that long-term smoking may impact immune responses at the systemic level, and that NK cells are involved [ 250 ]. There is ample evidence showing direct negative effect of cigarette smoke on NK cell cytolytic capacity, as well as on their ability to produce inflammatory cytokines in response to microbial agents.…”
Section: Effects Of Cigarette Smoke Exposure On the Immune Systemmentioning
confidence: 99%
“…Our research group has previously characterized systemic neutrophil mobilization, the CXC chemokine, the growth related oncogene-alpha (GRO-α) and interleukin(IL)-17A (formerly known as IL-17) in COPD during stable disease and exacerbations. [30][31][32] At this systemic level, the average IL-17A concentration during stable disease is substantially lower in smokers with COPD than in controls, especially in the smokers with COPD whose lungs have been colonized by airway pathogens. 30 The long-term alterations in IL-17 levels in COPD patients have not been studied.…”
Section: Biomarkersmentioning
confidence: 99%